2011
DOI: 10.1093/ejo/cjr043
|View full text |Cite
|
Sign up to set email alerts
|

In vitro orthodontic bracket bonding to porcelain

Abstract: This in vitro study investigated the influence of using different combinations of bracket, adhesive, and light-curing source on the tensile bond strength to porcelain and on failure patterns at debonding. Tensile tests were performed using: one ceramic bracket versus one metal bracket, two orthodontic composites; type bisphenol A-glycidyldimethacrylate and urethane dimethacrylate (UDMA), and four light-curing units with the same range of emission spectrum but various light intensities: three light-emitting dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 16 publications
2
26
1
Order By: Relevance
“…The results showed that significant differences were observed between LED and QTH regardless of the thermocycling and silane condition. These results are in line with those of previous studies, which also found significant differences between QTH and LED units (8)(9)(10). Other study showed that photo-activation is dependent on the radiant exposure (16).…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that significant differences were observed between LED and QTH regardless of the thermocycling and silane condition. These results are in line with those of previous studies, which also found significant differences between QTH and LED units (8)(9)(10). Other study showed that photo-activation is dependent on the radiant exposure (16).…”
Section: Discussionsupporting
confidence: 93%
“…1,2 This has encouraged orthodontists to test several different protocols with respect to bonding brackets to different dental restorations (specifically porcelain/ceramic restorations). Bonding orthodontic brackets to porcelain/ceramic surfaces presents a higher degree of failure when compared to bonding to enamel.…”
Section: Introductionmentioning
confidence: 99%
“…Many times this is granted to the porcelain type and surface conditioning, bracket material (base design, retention mode), properties of the bonding adhesive, and the light-curing source, as well as the skill of the clinician. 2,3 Also, adequate bond strength is desired with easy removal to avoid damage of the restored teeth. 4,5 Several techniques have been used to bond brackets to porcelain surfaces and these differ in surface preparation and bonding agent applied.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining sufficient bond strength is difficult when using only mechanical conditioning procedures with diamond stone burs, sandblasting, or sandpaper discs, and all these procedures damage the glazed surface of the ceramic restoration. [4][5][6][7][8][9][10][11] A combination of acids and silane coupling agent is recommended for chemical preparation of the glazed ceramic surface before bonding. [12][13][14] Silane enhances bond strength by increasing the chemical bond between the resin composite and the ceramic material.…”
Section: 4mentioning
confidence: 99%